What are the Implications for Policy Makers? A Systematic Review of the Cost-Effectiveness of Screening and Brief Interventions for Alcohol Misuse in Primary Care - Angus, Colin; Latimer, Nicholas; Preston, Louise; Li, Jessica; Purshouse, Robin (Frontiers in Psychiatry, 2014)
Introduction The efficacy of screening and brief interventions (SBI) for excessive alcohol use in primary care is well established; however evidence on their cost-effectiveness is limited. A small number of previous reviews have concluded that SBI programmes are likely to be cost-effective, but these results are equivocal and important questions around the cost-effectiveness implications of key policy decisions such as staffing choices for delivery of SBIs and the intervention duration remain unanswered. Methods Studies reporting both the costs and a measure of health outcomes of programmes combining screening and brief interventions in primary care were identified by searching MEDLINE, EMBASE, Econlit, the Cochrane Library Database (including NHS EED), CINAHL, PsycINFO, Assia and the Social Science Citation Index and Science Citation Index via Web of Knowledge. Included studies have been stratified both by delivery staff and intervention duration and assessed for quality using the Drummond checklist for economic evaluations. Results The search yielded a total of 23 papers reporting the results of 22 distinct studies. There was significant heterogeneity in methods and outcome measures between studies; however almost all studies reported SBI programmes to be cost-effective. There was no clear evidence that either the duration of the intervention or the delivery staff used had a substantial impact on this result. Conclusion This review provides strong evidence that SBI programmes in primary care are a cost-effective option for tackling alcohol misuse.